Studies on the Oestrous Cycle of Camel (Camelus dromedarius) - M.M. Alfuraiji (Journal of Agricultural and Marine Sciences, 1999)
The aim of this study was to investigate the oestrous cycle of the Arabian camel. Eight female camels (Majaheem) were used. Daily blood samples were collected for 60 days to measure Oestradiol - 178 (E2) and progesterone (P4) levels using radioimmunoassays. The duration of the follicular wave cycle ranged from 25-30 days and the length of oestrous from 5-7 days. P, levels were low (<3.2 nmol/l) throughout the cycle, while E2 levels were high during oestrous. The corpus luteum was therefore not present during the natural cycle suggesting that Arabian camels experienced induced ovulation.